The first voyage of Giovanni da Empoli to India: Mercantile culture, Christian faith, and the early production of knowledge about Portuguese Asia. (February 2019) - Salonia, Matteo
Giovanni da Empoli, a Florentine agent and merchant, was among the first Europeans to travel by an exclusively maritime route to India. This article focuses on Giovanni's first voyage to the East (1503–1504), during which he visited several ports along the Malabar coast. By examining Giovanni's letter to his father, this contribution explores his (re)emerging identities, and in particular his mercantile outlook and his Christian faith, which suggest a diversity of value systems and agendas among 'the Portuguese'. The experience of Giovanni is significant also because it represents an instance of production and transfer of knowledge about 'the Indies' in early Cinquecento Europe. As suggested by other contemporary sources concerning Giovanni, this circulation of knowledge did not take place only in writing, but also orally, in formal and informal conversations that Giovanni had with a variety of interested interlocutors both in Florence and elsewhere.